Do COVID-19 related primary emotions affect risk perceptions, efficacy beliefs, and information seeking and behavior? Examining emotions as audience segments - Turner, Monique M.; Lim, Jong In; Jang, Youjin; Heo, Ruth Jin-Hee; Ye, Qijia; Kim, Miyeon; Lapinski, Maria Knight; Peng, Tai-Quan (Frontiers in Communication, 2024)
Introduction Primary emotions among the populace during global health crises, such as the COVID-19 pandemic, provide valuable insights. Guided by appraisal theories of emotions, this study explores emotional segmentation by mapping primary emotions related to COVID-19 and investigating their impact on cognitive and behavioral outcomes, including risk perceptions, efficacy beliefs, behavioral intentions, prevention behaviors, and information seeking/avoidance. Methods Study 1 surveyed young adults (N = 1,368) to investigate their emotions about COVID-19 and examine the effect of these emotions on risk perceptions, efficacy beliefs, and behavioral intentions regarding mask-wearing and physical distancing. Study 2 replicated Study 1 with a quota-based national sample of U.S. adults (N = 8,454) and further tested the effect of primary emotions on preventive behaviors and information seeking/avoidance. Results Results indicated that most people experienced negative emotions, such as sadness, anger, and anxiety. These emotions were associated with varying levels of risk perceptions, efficacy beliefs, behavioral intentions, actual behaviors, and information seeking/avoidance. Notably, across both studies, anxious individuals demonstrated more favorable health-related perceptions and behavioral outcomes compared to those experiencing anger. Discussion These findings offer insights into the emotional experiences of individuals during the COVID-19 pandemic and highlight the significant impact of these emotions on risk perceptions and health-related behaviors. Understanding these emotional responses can inform public health strategies and communication efforts during health crises.